Deskripsi gaya hidup lansia yang tinggal bersama keluarga Dan di pstw khusnul khotimah - Siti - Zuraida; Ari Pristiana Dewi; Ganis - Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to describe the elderly’s lifestyle who lived with family and live at PSTW Khusnul Khotimah. This research used descriptive design with survey approach. Sample of research in family taken by  cluster sampling technique on 97 people and in PSTW with total sampling technique on 63 people. The instrument used was a questionnaire which have been tested for validity and reliability. Data analysis used univariate. The results of the research about lifestyle have shown that eating pattern of elderly were healthy (family: 57,7%; PSTW: 65,1%), physical activity and sport of elderly were active (family: 50,5%; PSTW: 58,7%), sleep and rest of elderly were enough (family: 79,4%; PSTW: 68,3%), smoking habit of elderly were high (family: 50,5%; PSTW: 50,8%), spiritual state of elderly were very good (82,5%; PSTW: 100%).This research recommended to family and the staff of PSTW for maintaining and increasing life support to elderly. Keyword: Elderly, family, lifestyle, PSTW (Panti Sosial Tresna Werdha)